Impact of metal nanoparticles biosynthesized using camel milk on bacterial growth and copper removal from wastewater - Al-Mohaimeed Amal Mohamed; El-Tohamy Maha Farouk; Moubayed Nadine Mohamad Safouh (Green Processing and Synthesis, 2025)
This study investigates the potential of zinc oxide (ZnO) and nickel oxide (NiO) nanoparticles (NPs), biosynthesized from camel milk, to combat bacterial resistance and enhance heavy metal removal from water. The antimicrobial efficacy against various pathogens, including Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Methicillin-resistant Staphylococcus aureus, Pseudomonas aeruginosa, and Candida tropicalis were studied. Characterization of the NPs was conducted using UV-vis, Fourier transform infrared, X-ray diffraction, transmission electron microscope, and atomic force microscopy techniques. Results showed that ZnO NPs exhibited the highest antimicrobial activity, with an inhibition zone of 16 mm against Pseudomonas aeruginosa and 13 mm against Candida tropicalis, while NiO NPs displayed reduced activity against all selected microorganisms. Additionally, ZnO NPs demonstrated an impressive Cu(ii) ion removal rate of 96.76% at pH 8.4, with a contact time of 90 min, using 0.5 g·L−1 of adsorbent at an initial concentration of 200 mg·L−1. Adsorption kinetics followed the pseudo-second-order model, with isotherm data fitting the Langmuir model (Q max = 100.0 mg·g−1, R 2 = 0.9905). Thermodynamic analysis indicated an exothermic process (∆H° = −4,127.4 J·mol−1) and spontaneous physical adsorption. Future research should focus on scaling up the biosynthesis of ZnO NPs for practical antimicrobial therapies and wastewater treatment technologies, alongside exploring their long-term environmental impact.